Linking cultural ecosystem service and urban ecological-space planning for a sustainable city: Case study of the core areas of Beijing under the context of urban relieving and renewal. (February 2023) - Zheng, Shanwen; Yang, Shengjie; Ma, Moheng; Dong, Jun; Han, Baolong; Wang, Jianqiang
Highlights: Community-level ecological space is most frequently used but is highly lacking. A supply/demand approach can inform effective ecological space planning strategies. The spatial distribution of cultural ecosystem services in the urban core is uneven. Spatial proximity to eco-space with historical value affects people's perception. Integrating cultural ecosystem services into planning can help achieve sustainability. Abstract: Planning and managing ecological space within the high-density mega-city is essential for ensuring ecological sustainability and contributing to residents' well-being. However, the relationship between ecological space and people's perception of cultural ecosystem services (CES) is still unclear. This research investigated the current situation of the ecological space within the core area of Beijing (CAB) and explored people's use habits and their levels of CES perception. Results showed that (1) the most frequently used ecological space was the community-level ecological space. However, so far, its provision was highly lacking; (2) Residents living along the central axis of Beijing tended to perceive a higher level of CES. However, the overall perceived value of education had the lowest scores in the CAB; (3) Among them, the "cultural values" perception was significantly affected by the spatial vicinity of ecological space with historical value. The proper conservation development of historical ecological space and improved residents' accessibility can be effective methods to promote CES perceptions of the residents in the core area. The findings of this study contribute to the high-density area to implement urban planning from the perspective of people's CES demands under the context of urban renewal.